The application of green roof for stormwater quantity and quality improvement - Noor Suraya, Romali; Othman, N. S.; Mhd Ramli, N. N. (IOP Publishing Ltd., 2021)
The use of green roof is becoming increasingly worldwide because of its environmental, economic, and aesthetic benefits. The ability to retain storm water and improve the quality of effluent flow are the important characteristics of green roof. It is viewed as a best technology to minimize the negative impact of urbanization. However, the application of green roof in Malaysia is less and literatures regarding these is limited. An attempt has been made to evaluate the performances of green roof in improving the water quantity and quality of stormwater runoff. A lab-scale green roof with five component layers which are vegetation layer using creeping ox-eye and beach morning glory, topsoil substrate layer, non-woven geotextile filter layer, drainage plate layer and liquid waterproofing layer was used. Results indicated that the green roof with creeping ox-eyes shows a better performance in reducing peak flow with as high as 41% percentages of reduction compared to beach morning glory (15%). On the other hand, the green roof with beach morning glory manage to improve the concentration of COD up to 99% improvement while the green roof with creeping ox-eye shows a better performance in improving BOD with 17% reduction.